STRATEGI POSITIONING KARTU PRABAYAR SIMPATI, IM3, XL, DAN 3 (Tri) BERDASARKAN PERSEPSI KONSUMEN - Nandang Bekti Karnowati; Irwan Saputro (JURNAL EKONOMI, 2018)
Perception is very important in helping evaluate the positioning strategy of product and helping to take action change the marketing strategy to win the market. Product that succeed has a good perception in the minds of consumers will make customers trust and so that a desire to buy the product will arise. This study aims to analyze the factors that consumers consider in choosing a prepaid GSM card. In addition, this study also aims to analyze the brand positioning of the existing prepaid GSM cards based on consumer perceptions. This research uses factor analysis and correspondent analysis methods. The research sample is 100 respondents who use prepaid GSM cards. The results showed that there are 3 factors to consider in choosing a prepaid GSM card, namely prestige, promotion and technology factors. Then the results of the correspondence analysis show that the IM3 prepaid GSM card has the advantage of easy-to-get SIM card attributes, attractive program promos and attractive television advertisements. XL prepaid GSM cards have the advantages of full-featured attributes, well-known companies and brands and attractive television advertisements. The GSM prepaid 3 (Tri) card has the advantage of the multiple quota bonus attribute and the Simpati prepaid GSM card has the advantage of having a strong and stable signal attribute and easy and satisfying operator services. Kata kunci : Positioning, Consumer perception, prepaid GSM SIM card